EAZY Digital Accreditation System Evaluation and its Contribution to Digital Citizen: Evidence from POLTESA - Runik Machfiroh; Akhmad Fauzi; Yusza Reditya Murti; Hasbi Syuhada (Advance Sustainable Science Engineering and Technology, 2026)
Accreditation processes in higher education institutions are often inefficient, particularly in border regions like Indonesia, where limited infrastructure and resources pose significant challenges. This study evaluates the EAZY Digital Accreditation System at POLTESA, a State Polytechnic in West Kalimantan one of border region of Indonesia. using a mixed-methods approach and Social Return on Investment (SROI) analysis to assess its operational and social impacts. The research combines qualitative stakeholder surveys with quantitative SROI metrics to measure efficiency gains and cost savings. Key findings reveal an SROI ratio of 3.948:1 in Year 1, increasing to 11.1:1 by Year 3, along with IDR 592 million in savings. The results highlight the system’s success in improving accreditation efficiency, offering valuable lessons in digital transformation. Furthermore, the implementation of the digital accreditation system enhances digital citizenship by fostering greater transparency, accountability, and participatory governance in educational institutions. These findings suggest that digital accreditation systems can be scaled to other institutions, bridging gaps in educational quality and supporting national resilience.